Biocatalysis in seawater: Investigating a halotolerant ω‐transaminase capable of converting furfural in a seawater reaction medium - Kelly, Stephen A.; Moody, Thomas S.; Gilmore, Brendan F. (Engineering in life sciences, 2019)
The increasing demand for freshwater and the continued depletion of available resources has led to a deepening global water crisis. Significant water consumption required by many biotechnological processes contributes to both the environmental and economic cost of this problem. Relatively few biocatalytic processes have been developed to utilize the more abundant supply of seawater, with seawater composition and salinity limiting its use with many mesophilic enzymes. We recently reported a salt tolerant ω‐transaminase enzyme, Ad2‐TAm, isolated from the genome of a halophilic bacterium, Halomonas sp. CSM‐2, from a Triassic period salt mine. In this study we aimed to demonstrate its applicability to biocatalytic reactions carried out in a seawater‐based medium. Ad2‐TAm was examined for its ability to aminate the industrially relevant substrate, furfural, in both seawater and freshwater‐based reaction systems. Furfural was aminated with 53.6% conversion in a buffered seawater system, displaying improved function versus freshwater. Ad2‐TAm outperformed the commonly employed commercial ω‐TAms from Chromobacterium violaceum and Vibrio fluvialis, both of which showed decreased conversion in seawater. Given the increasingly precarious availability of global freshwater, such applications of enzymes from halophiles have the ability to reduce demand for freshwater in large‐scale industrial processes, delivering considerable environmental and economic benefits.